The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1523/jneurosci.2215-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Site of a Motor Memory Shifts with Consolidation

Abstract: The basis for the consolidation of memory is a controversial topic, particularly in the case of motor memory. One view is that motor memory is transferred, partially or completely, to a new location during the consolidation process ("systems consolidation"). We investigated this possibility in a primitive motor system, the vestibulo-ocular reflex (VOR). In the simple circuitry of the VOR, there are relatively few possible storage sites for memory. We partially blocked excitatory neurotransmission in the cerebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
105
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 42 publications
11
105
2
Order By: Relevance
“…Interestingly, a more natural form of cerebellar learning such as VOR adaptation does not display robust savings (Miles and Lisberger, 1981), perhaps because mossy fiber synapses onto the vestibular nuclei already exist. Nonetheless, recent studies of VOR adaptation showing that the effects of reversible cerebellar cortex lesions depend on the amount of training are generally consistent with these findings, further underscoring the parallels between eyelid conditioning and VOR adaptation (Kassardjian et al, 2005;Shutoh et al, 2006).…”
Section: Functional Contributions Of Plasticity In the Ainsupporting
confidence: 61%
“…Interestingly, a more natural form of cerebellar learning such as VOR adaptation does not display robust savings (Miles and Lisberger, 1981), perhaps because mossy fiber synapses onto the vestibular nuclei already exist. Nonetheless, recent studies of VOR adaptation showing that the effects of reversible cerebellar cortex lesions depend on the amount of training are generally consistent with these findings, further underscoring the parallels between eyelid conditioning and VOR adaptation (Kassardjian et al, 2005;Shutoh et al, 2006).…”
Section: Functional Contributions Of Plasticity In the Ainsupporting
confidence: 61%
“…The training history-dependent transfer of memory trace of adaptation has been demonstrated by pharmacological shutdown experiments in the HOKR in mice (Shutoh et al, 2006) and horizontal vestibulo-ocular reflex (HVOR) in cats (Kassardjian et al, 2005) and monkeys (Anzai et al, 2010). One may speculate that flocculus shutdown would increase the spontaneous discharges of flocculus target vestibular nuclear neurons, alter the general performance of the HOKR/ HVOR neural circuitry, and consequently may affect HOKR/HVOR gains.…”
Section: Neural Mechanisms For Memory Trace Transfermentioning
confidence: 99%
“…One may speculate that flocculus shutdown would increase the spontaneous discharges of flocculus target vestibular nuclear neurons, alter the general performance of the HOKR/ HVOR neural circuitry, and consequently may affect HOKR/HVOR gains. However, we consider that such a possibility is unlikely, because effects of floccular lidocaine infusions were specific to the gains changed by adaptation (Nagao and Kitazawa, 2003;Shutoh et al, 2006;Anzai et al, 2010), and floccular CNQX infusions, which would only mildly affect the spontaneous discharges of Purkinje cells, induced similar effects on the adaptation as those of lidocaine (Kassardjian et al, 2005). These studies consistently suggest that the memory trace of adaptation induced by 1-2 h of training is located in the flocculus and that memory trace is transferred to the vestibular nuclei after days of training.…”
Section: Neural Mechanisms For Memory Trace Transfermentioning
confidence: 99%
“…It has been also suggested that in long-lasting visuo-vestibular training, motor memory is stored at different cerebellum and vestibular nuclei loci, resulting in memory encoding first in the cerebellum that is then "transferred" to vestibular nuclei (Broussard et al 2011;Galiana 1986;Kassardjian et al 2005;Raymond et al 1996). In addition, a recent model (Menzies et al 2010) indicates that the "transfer" of motor memory may occur immediately after memory encoding, which is detectable within minutes after the start of the conditioning training.…”
Section: Cerebellar and Possible Extra-cerebellar Plastic Sites For Vmentioning
confidence: 99%